Aorto-bi-Femoral Bypass for Aorto-Iliac Occlusive Disease: Recent Experience at the National Institute of Cardiovascular Diseases (NICVD) - Bashar, AHM; Hossain, GMM; Hakim, E; Mondol, NC; Sabah, MN; Hossain, MF; Dey, NK; Samad, S; Mamun, AA; Haroon, K; et al. (Cardiovascular Journal, 2012)
Background & Objectives: Aorto-bi-femoral bypass is one of the most important surgical strategies in vascular surgical practice. The procedure is employed in surgical revascularization for both stenotic and aneurysmal diseases involving the aorto-iliac segment. The present study was carried out to analyze our recent experiences with this procedure for aorto-iliac occlusive diseases (AIOD) at the National Institute of Cardiovascular Diseases (NICVD). Materials and Methods: Over a period of 3 years (April 2008 to March 2011), a total of 47 patients underwent aorto-bi-femoral or aorto-bisiliac bypass grafting for AIOD using a Y-graft prosthesis. The mean age of the patients was 46.4 years (range 25-75 years). Thirty eight of the patients were male and the remaining 9 were female. A retroperitoneal approach was used in 27 patients. In the remaining 20 patients, the operation was done using a transperitoneal approach. A Gelatin-coated Dacron Y-graft prosthesis was used in 43 (5 of which were silver-coated prosthesis) patients while PTFE (Polytetrafluoroethylene) prosthesis was used in the remaining 4 patients. The operation was carried out under epidural anesthesia with sedation in most cases. Results: The operation was well-tolerated in all patients. There was no intraoperative mortality in this series. Two patients died in the immediate post-operative period- one due to myocardial infarction and the other due to acute renal shut-down leading to renal failure accounting for a mortality rate of 4.3%. Wound infection and lymphorrhoea at the groin incision site were the two main immediate post-operative complications. There was no incidence of graft infection in this series. Twelve patients were available for post-operative follow-up up to 2 years. Out of them, 5 patients returned with occluded grafts 8-23 months after the operation. Three of these patients underwent graft excision with re-do Y-graft bypass. The remaining two were treated with extra-anatomic bypass (Axillobifemoral). Conclusions: Aorto-bi-femoral bypass is an effective surgical strategy for occlusive diseases involving the abdominal aorta and the iliac arteries. The procedure is well-tolerated with a low incidence of early post-procedural complications and graft failure. However, poor adherence of the patients to follow-up remains a significant obstacle for evaluating the long-term outcome of this procedure. Keywords: Aorto-Iliac Occlusive Disease; Aorto-bi-Femoral Bypass. DOI: http://dx.doi.org/10.3329/cardio.v4i1.9386 Cardiovasc. J. 2011; 4(1): 26-31